Peran fitur virtual try-on dan ulasan pelanggan online dalam meningkatkan niat beli konsumen: Studi pada produk lipstik Maybelline di Shopee - Zipora Marbun; Heddry Purba; Francis Hutabarat (Nur Science Institute, 2026)
This study examines the influence of the virtual try-on feature framed within the Unified Theory of Acceptance and Use of Technology (UTAUT) and online customer reviews on consumers' purchase intention toward Maybelline lipstick on Shopee. A quantitative approach was employed, with data collected from 114 active Shopee users in Parongpong District, West Bandung Regency. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS software. The results indicate that effort expectancy, performance expectancy, and online customer reviews have a positive and significant influence on purchase intention in the context of using the virtual try-on feature on the Shopee platform. Of the three variables examined, online customer reviews were identified as the dominant factor influencing consumers' purchase intention. These findings indicate that integrating augmented reality technology via the virtual try-on feature, supported by a credible customer review system, can reduce consumer uncertainty and enhance consumer confidence when purchasing cosmetic products online. This study provides practical implications for e-commerce platforms and cosmetic companies, particularly in optimizing interactive digital features and strengthening customer review management systems as strategies to enhance consumers' purchase intention in online marketplaces.